Quantum chemical determination of molecular geometries and spectral investigation of 4-ethoxy-2, 3-difluoro benzamide. Issue 11 (November 2019) - Vidhya, V.; Austine, A.; Arivazhagan, M.
Abstract: The present work reports the application of density functional theory (DFT) at B3LYP with various basis sets which provide the relationship between the structural and spectral properties of 4-ethoxy-2, 3-difluoro benzamide (4EDFB). A Complete vibrational analysis has been performed at the density functional theory (DFT) method with various basis sets in the ground state. The results of vibrational wave numbers are in good agreement with the experimental spectra (Infrared and Raman). Energy gap of the molecule is evaluated using frontier molecular orbital energies (HOMO-LUMO). The frontier energy gap value reveals the chemical reactivity and intermolecular charge transfer occur within the molecule. Global chemical descriptors provide the local and global softness and local reactivity parameters used to identify the nucleophilic and electrophilic behavior of a specific site within the compound. The dimer structure is performed to evaluate the intermolecular hydrogen bond (O–H–O). The title molecule is capable of receiving second harmonic generation (SHG) is due to high value of hyperpolarizability indicates the NLO activity of the molecule. Apart from NLO entities, aromaticity and the molecular electrostatic potential surface (MEP) explain the hydrogen bonding and provide the reactive behavior of the molecule. The Mulliken population analysis leads to redistribution of electron density in the ring. Abstract : Organic chemistry; Pharmaceutical chemistry; Theoretical chemistry; DFT; NLO; MEP; HOMA index; Dimer